Sajian Lagu Ribu Ribu Dalam Acara Pernikahan di Daerah Rambang Niru Muara Enim - Putra, Rian Dwi Pratama; Firmansyah, Dedy; Firmansyah, Feri (Indonesian Research Journal on Education, 2023)
Folk songs have moral and ethical values that are very useful, to be used as a life guide for all children of the nation for an ideal stage in character building. Regional songs are often called traditional songs, each song in the archipelago has its uniqueness, be it in terms of beauty, the uniqueness of melodies, instruments, lyrics, and harmonies. The method used in this research is a qualitative descriptive method, which presents data using sentences in the form of narrative text. While the approach of this researchwith a direct approach using musicological science. The originator of the thousand songs is still unknown until now because the songwriter just sparked when doing the tembangan and according to information from the previous story the song ribu ribu the creator has died therefore the ribu ribu song has no patent owner but can be preserved. The ribu ribu song is well developed and very well received because this song includes tembangan or another word for tembangan according to the local language or Rambanglanguage is "Betembang" which means singing, until now the ribu ribu songs is still used in weddings. The use of ribu ribu songs at weddings in the Rambang Niru area is a tradition of the local community because ribu ribu songs are used to release the bride and groom because they are married and will live a new life, ribu ribu songs are a blend of between two families who feel happy because the child has found a soul mate.